Urgensi Regulasi Penyalahgunaan Deepfake Sebagai Perlindungan Hukum Korban Kekerasan Berbasis Gender Online (KBGO) - Rohmawati, Indah; Junaidi, Amir; Khaerudin, Ariy (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the urgency of regulations specifically addressing the misuse of deepfake technology as a form of legal protection for victims of Online Gender-Based Violence (GBV). Artificial intelligence (AI)-based deepfake technology can create highly realistic visual content but is also prone to misuse, especially for non-consensual pornography and the dissemination of false information that damages individuals' reputations. This research employs normative legal methods, examining Indonesian laws and regulations such as the Electronic Information and Transaction Law (EIT Law), the Pornography Law, the Personal Data Protection Law (PDP Law), and the Criminal Code (KUHP). The results indicate that, although there are existing regulations that could apply, there are no specific regulations addressing deepfake technology, resulting in suboptimal victim protection. Specific regulations are necessary to provide preventive protections, restrict the creation and dissemination of illegal deepfake content, and enforce stricter sanctions. Additionally, increasing digital literacy and public legal awareness is crucial as a preventive measure. With comprehensive regulations, it is hoped that the rights of GBV victims will be better protected and the misuse of deepfake technology minimized.